Determination of alpha naphthyl acetate esterase activity in peripheral blood leucocytes of kangal fish (garra rufa) - Hasan Hüseyin Dönmez; Emrah Sur; Murat Boydak (Eurasian Journal of Veterinary Sciences)
The aim of the study was to determine the percentage of peripheral blood ANAE (+) lymphocytes in Kangal fishs by using an alpha-naphtyl acetate esterase procedure. Peripheral blood samples taken from 12 Kangal fishs were used. The percentage of ANAE positive lymphocytes was 62.06%. There was a diffuse granular positivity against ANAE demonstration in monocytes and granulocytes; however negative reaction were observed in erythrocytes and thrombocytes.